MANAGING FLOOD RISKS: LESSONS FROM KEKO MACHUNGWA INFORMAL SETTLEMENT IN DAR ES SALAAM, TANZANIA - Tumpale Sakijege Sakijege (Faculty of Geography, Universitas Gadjah Mada, 2013)
Globally, world urban population has been increasing and by 2050 it is expected to reach70% of the world population. This is a challenge because new settlements are emerging andmost of them are taking place informally in developing countries. Forms of urbanization indeveloping countries are not in favor of poor people. As a result, majorities are forced toreside informally in areas prone to natural hazards in general and floods in particular.Literatures prove that informal settlements are a major factor in the increase of floodsbecause most of them lack of basic infrastructures and there is poor coordination from thedevelopment activities. These together contribute to the increase of vulnerability of informalsettlement inhabitants into different risks associated with floods as a result of climaticchange. The paper therefore assesses surroundings of informal settlements under theumbrella of factors that cause risks and how they are managed and spell out relevant policyimplications. Findings show that factors that increase flood associated risks in the settlementinclude: housing densification, solid waste management, sewers and drains management,blocked streams, water sources, livestock keeping, and accessibility.